In-Vitro Antibacterial Properties and Pre-Liminary Phtytochemical Analysis of Amomum subulatum Roxburg (Large Cardamom) - Mustapha A. Tijjani, Goni A. Dimari, Sule W. Buba, Irfan Z. Khan (Journal of Applied Pharmaceutical Science)
The efficacy of methanolic seed extracts of Amomum subulatum Roxb. activity against bacterias such Staphylococcus aureus, Streptococcus pneumoniae, Bacillus subtilis, Salmonella typhi, Klebsiella pneumoniae, Pseudomonas aerugenosa and Candida albican senegalensis was studied. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extracts was determined using standard methods. Results obtained showed considerable inhibition against the bacteria tested except Salmonella pyrogenes and Escheria Coli which showed considerable resistance at all concentrations of the extract. It can also observe that the extract exhibited greater inhibition on Klebsiella pneumonia and Pseudomonas aerugenosa (18±0.2 and 17±0.3). However the standard antibacterial drug tetracycline exhibit superior activity than the extract. Both the MICs and MBCs of the extract ranges from 50 to 200 mg/ml. Its further reveals that Bacillus subtilis, Klebsiella pneumonia and Staphylococcus aureus exhibit broadest activity at MIC and MBC concentrations of 50mg/ml. While the rest Salmonella typhii and Pseudomonas aerogunosa and candida albicans of the bacteria shows negative turbidity and resistance at MIC and MBC of 100mg/ml. This activity was indicative of the possible means of finding pure active principles from natural source with possible high potency that could serve as a lead to the pharmaceuticals. The low concentration (MIC and MBC) activity of the methanolic extracts give credence and scientific base for the claim therapeutic capabilities of Amomum subulatum as an anti-bacterial agent. The extract concentrate yield of the methanolic extracts was estimated to be 9.8%w/w which is brown in colour and oily in texture. Preliminary screening analysis of the powdered methanolic seed extracts showed the presence of Carbohydrate, tannins, cardioactive glycosides, tepenes, flavonoids, alkaloids and saponins. Anthraquinone was not found in the extract. The study provides the basis of use of this plant Amomum subulam in treatment of infections caused by pathogens (bacteria) and the phytochemical found are implicated in having anti-bacterial properties.
Keywords: Anti-bacterial, phytochemical, Amomum subulatum, extract.